2015
DOI: 10.1007/s10584-015-1514-z
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of freshwaters to browning in response to future climate change

Abstract: Many boreal waters are currently becoming browner with effects on biodiversity, fish production, biogeochemical processes and drinking water quality. The question arises whether and at which speed this browning will continue under future climate change. To answer the question we predicted the absorbance (a 420 ) in 6347 lakes and streams of the boreal region under future climate change. For the prediction we modified a numerical model for a 420 spatial variation which we tested on a temporal scale by simulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
120
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(122 citation statements)
references
References 38 publications
1
120
0
1
Order By: Relevance
“…The five climate change treatments therefore ranged from a modest scenario with 1°C warming and 50% increase in absorbance to the most extreme scenario of 5°C warming and 250% increase in absorbance relative to the control. This latter scenario represents the upper range of warming predictions made by the IPCC‐reports, but implies rates of change over the coming century that are well below the fastest rates currently observed for both lake temperature (O'Reilly et al ) and browning (Weyhenmeyer et al ).…”
Section: Methodsmentioning
confidence: 86%
“…The five climate change treatments therefore ranged from a modest scenario with 1°C warming and 50% increase in absorbance to the most extreme scenario of 5°C warming and 250% increase in absorbance relative to the control. This latter scenario represents the upper range of warming predictions made by the IPCC‐reports, but implies rates of change over the coming century that are well below the fastest rates currently observed for both lake temperature (O'Reilly et al ) and browning (Weyhenmeyer et al ).…”
Section: Methodsmentioning
confidence: 86%
“…Likewise, Weyhenmeyer et al [] showed that direct inputs of DIC from the terrestrial surroundings of a lake have a stronger influence on CO 2 concentrations in lake water than do lake internal CO 2 production. As precipitation and runoff have shown an overall increase across Sweden over the past few decades, in particular during the 1990s and 2000s [ Bengtsson and Rana , ; Lindström and Bergström , ; Weyhenmeyer et al ., , ], we suggest that most waters now receive proportionally more shallow groundwater compared to deep groundwater [ Laudon et al ., ] (Figure ). Such an increase most likely results in a DOC concentration increase in surface waters as DOC concentration in soil profiles tends to increase toward the top soil layers [ Grabs et al ., ; Kaiser and Kalbitz , ].…”
Section: Discussionmentioning
confidence: 99%
“…Mesocosm experiments provide a strong predictive basis for assessing the direction and strength of responses to ongoing environmental changes (Jeppesen et al., 2012; Spivak, Vanni, & Mette, ; Stewart et al., ). Our experiment captures the seasonal community changes under a predicted gradient of climate warming and brownification conditions in northern temperate lakes (IPCC, ; Monteith et al., ; Weyhenmeyer et al., ). However, it is important to stress that scaling up results to future climate change scenarios for the next decades should be done with caution (Stewart et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…These warming conditions followed temperature projections from the Intergovernmental Panel on Climate Change for this century (IPCC, ). Our brownification scenarios were based on historical trends from southern Swedish lakes (Hansson et al., ), which lie within the range of the future projected increase in brownification for Swedish lakes (Weyhenmeyer et al., ).…”
Section: Methodsmentioning
confidence: 99%